2022
DOI: 10.3390/s22239199
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Integral Imaging with Enhanced Lateral and Longitudinal Resolutions Using Multiple Pickup Positions

Abstract: In this paper, we propose an enhancement of three-dimensional (3D) image visualization techniques by using different pickup plane reconstructions. In conventional 3D visualization techniques, synthetic aperture integral imaging (SAII) and volumetric computational reconstruction (VCR) can be utilized. However, due to the lack of image information and shifting pixels, it may be difficult to obtain better lateral and longitudinal resolutions of 3D images. Thus, we propose a new elemental image acquisition and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There have been various three-dimensional (3D) imaging techniques for acquiring full parallax images from a 3D scene; direct pickup in integral imaging [ 1 , 2 , 3 , 4 ], synthetic aperture integral imaging [ 5 , 6 ], light field imaging [ 7 , 8 ], lensless 3D imaging [ 9 , 10 ], and so on. In particular, lensless 3D imaging is free from diffraction and aberrations that occur in lens array-based acquisition methods, and has advantages over camera array or moving camera-based acquisition methods in point of view for cost effectiveness and system complexity.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various three-dimensional (3D) imaging techniques for acquiring full parallax images from a 3D scene; direct pickup in integral imaging [ 1 , 2 , 3 , 4 ], synthetic aperture integral imaging [ 5 , 6 ], light field imaging [ 7 , 8 ], lensless 3D imaging [ 9 , 10 ], and so on. In particular, lensless 3D imaging is free from diffraction and aberrations that occur in lens array-based acquisition methods, and has advantages over camera array or moving camera-based acquisition methods in point of view for cost effectiveness and system complexity.…”
Section: Introductionmentioning
confidence: 99%
“…These images are referred to as Elemental Images (EIs). 3D data can be digitally reconstructed from these multiple-perspective images using Computational Integral Imaging (CII) [8][9][10][11][12][13][14][15][16]. While Integral-Imaging can produce rich 3D data of the scene, it does not require the use of sources of illumination, as in time-of-flight cameras [17] or structured light imaging [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported to overcome the drawbacks of the integral imaging [2][3][4][5][6][7][8][9][10][11][12][13]. To improve the viewing resolution of 3D images, the moving array lenslet technique (MALT) [6] was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic aperture integral imaging (SAII) [7], which uses a camera array, can improve the viewing resolution of 3D images since each elemental image has the same resolution as the image sensor. In [8], the SAII is further merged with an axially distributed sensing method to improve the lateral and longitudinal resolutions of 3D objects. However, it is not cost-effective and there exists a synchronization problem between cameras.…”
Section: Introductionmentioning
confidence: 99%